A REVIEW OF HEALTHCARE CENTER - Siti Nur Fadhilah binti Masrom; Phang Yook Ngor; Ruzanita Mat Rani (Journal of Islamic, Social, Economics and Development, 2022)
Healthcare center is the first place people go when they need medical assistance. In Malaysia, healthcare is mainly under the Ministry of Health. The Malaysian government prioritizes healthcare growth and development and allocates some of the government's social development budget to public health care. Hence, public healthcare is available to all Malaysian citizens. For citizen, the fee for registration at public hospitals and clinics are almost free but patients can still receive the best treatment, medications, and services. So, the main purpose of this study is to illustrate a general review of the healthcare center in Malaysia. There have several points to elaborate which are the healthcare center, the healthcare team, the quality of the healthcare system, the Donabedian model, the dimensionless wellness, the patient care, the outpatient department as the primary care, primary care, and service at the outpatient department. There have 51 articles or theses of research were included in this paper. We classify papers according to the areas of application that are clear in the literature given that several papers propose or illustrate general approaches.